Cannabinoids in Audiogenic Seizures: From Neuronal Networks to Future Perspectives for Epilepsy Treatment - Lazarini-Lopes, Willian; Do Val-da Silva, Raquel A.; da Silva-Júnior, Rui M. P.; Cunha, Alexandra O. S.; Garcia-Cairasco, Norberto (Frontiers in Behavioral Neuroscience, 2021)
Cannabinoids and Cannabis-derived compounds have been receiving especial attention in the epilepsy research scenario. Pharmacological modulation of endocannabinoid system's components, like cannabinoid type 1 receptors (CB1R) and their bindings, are associated with seizures in preclinical models. CB1R expression and functionality were altered in humans and preclinical models of seizures. Additionally, Cannabis-derived compounds, like cannabidiol (CBD), present anticonvulsant activity in humans and in a great variety of animal models. Audiogenic seizures (AS) are induced in genetically susceptible animals by high-intensity sound stimulation. Audiogenic strains, like the Genetically Epilepsy Prone Rats, Wistar Audiogenic Rats, and Krushinsky-Molodkina, are useful tools to study epilepsy. In audiogenic susceptible animals, acute acoustic stimulation induces brainstem-dependent wild running and tonic-clonic seizures. However, during the chronic protocol of AS, the audiogenic kindling (AuK), limbic and cortical structures are recruited, and the initially brainstem-dependent seizures give rise to limbic seizures. The present study reviewed the effects of pharmacological modulation of the endocannabinoid system in audiogenic seizure susceptibility and expression. The effects of Cannabis-derived compounds in audiogenic seizures were also reviewed, with especial attention to CBD. CB1R activation, as well Cannabis-derived compounds, induced anticonvulsant effects against audiogenic seizures, but the effects of cannabinoids modulation and Cannabis-derived compounds still need to be verified in chronic audiogenic seizures. The effects of cannabinoids and Cannabis-derived compounds should be further investigated not only in audiogenic seizures, but also in epilepsy related comorbidities present in audiogenic strains, like anxiety, and depression.